2019
DOI: 10.3390/ijerph16101690
|View full text |Cite
|
Sign up to set email alerts
|

Poor Family Relationships in Adolescence and the Risk of Premature Death: Findings from the Stockholm Birth Cohort Study

Abstract: Poor family relationships during childhood have been shown to have long-term negative effects on an offspring’s health. However, few studies have followed the offspring to retirement age, and relatedly, knowledge about the link between poor family relationships and premature death is scarce. The aim of this study was to examine the association between poor family relationships in adolescence and the risk of premature death, even when considering other adverse childhood conditions. Prospective data from the Sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…As Alm et al state in their 2019 research, dysfunctional family relationships can have a negative impact on children’s emotional and social competence, which in turn can hinder healthy development and ultimately affect health [ 39 ]. In addition to positive relationships with the family, in other research, positive peer relationships were found to be an important factor in adolescent well-being [ 40 , 41 ]; therefore, it is important that the family is also involved or ensures that adolescents have a group of equals that favors their well-being.…”
Section: Discussionmentioning
confidence: 99%
“…As Alm et al state in their 2019 research, dysfunctional family relationships can have a negative impact on children’s emotional and social competence, which in turn can hinder healthy development and ultimately affect health [ 39 ]. In addition to positive relationships with the family, in other research, positive peer relationships were found to be an important factor in adolescent well-being [ 40 , 41 ]; therefore, it is important that the family is also involved or ensures that adolescents have a group of equals that favors their well-being.…”
Section: Discussionmentioning
confidence: 99%
“…However, although the present study showed that the association between poor family relationships in childhood and in-patient psychiatric care was weaker as the individuals grew older, it is possible that adverse family relationships in childhood may have other harmful consequences that last into late adulthood. Indeed, prior studies have reported links between poor parent–child relationships in childhood and physical health problems in mid-adulthood [ 3 , 9 ], and a recent study based on data from the SBC showed poor family relationships in adolescence to be linked with an increased risk of premature death up until late adulthood [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining cases were divided into two groups of about equal size to capture ‘good’ and ‘intermediate’ family relationships, again in a relative sense. This trichotomised measure of family relationships has been used previously [ 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily, adolescents who are faced with unsupportive familial relationships [60], hostility in the home [61] or may have a parent [62][63][64] or sibling with mental health issues [64] may be at greater risk for their own mental health concerns. Adolescents living in such environments are at an increased risk of suicide, substance use, mood disorders and issues with eating [2].…”
Section: Family Functioningmentioning
confidence: 99%